A systematic review on the teaching of electrodynamics (Research, Society and Development, 2022)
Physics teaching has been characterized by low rates of learning and approval. This perception is attributed by several researchers to the traditional teaching method used by schools. In this sense, this article aims to present a systematic literature review of works related to the teaching of electrodynamics in basic education, published in the main journals on Physics teaching, in recent years, in order to identify pedagogical proposals relevant to this area of ​​study. teaching. The results obtained show a growing increase in the amount of research on the teaching of electrodynamics in recent years, in which the most used didactic practices are those that involve experimentation and use of technological resources. Among the topics most discussed in these practices are simple electrical circuits, while the least discussed are generators and receivers.